Code Mixing Used by Kindergarten Students in Dharma Yudha National Plus School - Sifra Jenisa Murbi; Karnedi Karnedi; Maspufah Maspufah (Enlighted Journal, 2023)
Speaking by mixing two languages currently become a habit in national plus school which used both of English and Bahasa Indonesia in their teching and learning activities. The code mixing in early ages like kindergarten was very unique and interested to be analyzed. The purpose of this research was to identify the type of code mixing used and the factors caused the code mixing of the students’ conversation at the school. The research used descriptive qualitative methods. The data were the transcript of students’s conversation and the parents’ interview. The data were collected by using voice recorder and questionaire through google from. The data were analyzed by using three data analysis theory of data reduction, data display, and drawing conclusion. After analyzing the data, the results showed that there were seven uterances of insertion, eleven utterances of alternative, and seven congruent lexicalization of code mixing occured in students’ conversations. Then, the factors caused the code mixing in students’ conversation were situation and prestige factor bilingual factor which most of students speak both of English and bahasa indonesia not only at school but also at home, the speaker and partner speaking factor, the social community factors, the situation factor, vocabulary factor and prestige factors. Thus, situation factor and prestige factor were the dominants factor that mostly motivated students to mix their conversation in the class discussion and in their daily communication.